TRANSFORMING EDUCATION IN THE 5.0 ERA: A CASE STUDY ON THE DIGITAL READINESS OF ENGLISH LECTURERS AT POLYTECHNICS - Hidayad, Ferri; Ridayani, Ridayani; Purwanto, Muhammad Bambang; Agustinasari, Evi (Relawan Jurnal Indonesia, 2024)
This study evaluated the readiness of English lecturers at the Darussalam Polytechnic to face the transformation of digital learning in the 5.0 era. Using a retrospective case study approach, this study identified the factors that affect lecturers' readiness and the challenges they face in adopting digital technology in teaching. Data were collected through in-depth interviews and observations, which were analyzed using descriptive and thematic analysis techniques. The study results showed that English lecturers at the Darussalam Polytechnic have a positive attitude towards digital learning and show an increase in technological literacy due to the COVID-19 pandemic. However, the limitations of technological infrastructure and the need for continuous training remained significant challenges. This study concluded that lecturers' readiness to face digital transformation was quite significant, but it still needed to be improved through infrastructure improvement, continuous training, and institutional support. The results of this research are expected to contribute to the development of educational policies and teaching practices at the Darussalam Polytechnic and other higher education institutions in Indonesia.